DAMPAK PERATURAN KEHIDUPAN SISWA (PERDUPSIS) DALAM PEMBENTUKAN MENTAL KEPEMIMPINAN SISWA PENDIDIKAN PEMBENTUKAN BINTARA POLRI DI SPN POLDA JAWAR BARAT - Rahmawati, Evi; Widiastuti, Novi (Comm-Edu (Community Education Journal), 2024)
This study aims to: determine the planning of student life regulations (perdopsis) in the formation of mental leadership for the formation of the National Police NCO at SPN Polda West Java, find out the implementation of student life regulations (perdopsis) in the formation of mental leadership in education for the formation of the National Police NCO at SPN Polda West Java. , regulation of student life (perdupsis) in the formation of mental leadership in education for the formation of the National Police NCO at the SPN Polda West Java. The research method used in this research is descriptive qualitative. The technique used to collect data is using observation, interview and documentation techniques. Checking data using triangulation and member check. The result of this research is that the mental formation of student leadership provides a way for the NCO students to be able to build the foundation of leadership character in the field, the experience gained is in the form of additional characters in building other characters in the form of characters to be religious, honest, tolerant, disciplined in time, able to to learn independently, have a fairly high curiosity, be able to communicate and tolerate well and be able to take responsibility for what is obtained and carried out in the field.